Blood surface-enhanced Raman spectroscopy based on Ag and Au nanoparticles for nasopharyngeal cancer detection. (17th March 2016) - Lin, Duo; Ge, Xiaosong; Lin, Xueliang; Chen, Guannan; Chen, Rong
Abstract: This study aims to evaluate and compare the utility of blood surface-enhanced Raman spectroscopy (SERS) based on Au or Ag nanoparticles (NPs), respectively, for detection of nasopharyngeal cancer (NPC). A rapid home-made Raman system was employed for SERS measurement, and high quality SERS spectra can be recorded from blood plasma samples belonging to 60 healthy volunteers and 100 NPC patients, using both metallic NPs. The spectral differences under Ag-SERS measurement between the normal and cancer groups are more significant than Au-SERS. Principal component analysis combined with linear discriminant analysis (PCA-LDA) was used for differentiating the two blood groups with a diagnostic sensitivity and specificity of 90% and 95%, respectively, using Ag-SERS method, which has almost a 20% improvement in diagnostic specificity in comparison to Au-SERS. This exploratory study demonstrates that blood SERS based on Ag NPs is capable of achieving a better diagnostic performance for NPC detection, and has promising potential for improving NPC screening.